2018
DOI: 10.1113/ep087207
|View full text |Cite
|
Sign up to set email alerts
|

Chronic oral rapamycin decreases adiposity, hepatic triglycerides and insulin resistance in male mice fed a diet high in sucrose and saturated fat

Abstract: Excess adiposity is commonly associated with insulin resistance, which can increase the risk of cardiovascular disease. However, the exact molecular mechanisms by which obesity results in insulin resistance are yet to be understood clearly. The intracellular nutrient-sensing protein, mechanistic target of rapamycin (mTOR), is a crucial signalling component in the development of obesity-associated insulin resistance. Given that increased tissue activation of mTOR complex-1 (mTORC1) occurs in obesity, diabetes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…On the contrary, other studies revealed that enhancing macrophage autophagy by the mTOR inhibitor may be a viable therapeutic or preventative approach to inflammatory disease, obesity insulin resistance, and diabetes [44, 53]. Interestingly, the present study showed that rapamycin at a dose of 1 mg/kg/day exerts a positive effect on serum glucose in STZ plus high-fat diet-induced diabetic ApoE-/- mice, and the finding was supported by den Hartigh et al [16]. Further studies needed to investigate the effect of rapamycin on blood glucose in STZ plus high-fat diet-induced ApoE-/- mice.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the contrary, other studies revealed that enhancing macrophage autophagy by the mTOR inhibitor may be a viable therapeutic or preventative approach to inflammatory disease, obesity insulin resistance, and diabetes [44, 53]. Interestingly, the present study showed that rapamycin at a dose of 1 mg/kg/day exerts a positive effect on serum glucose in STZ plus high-fat diet-induced diabetic ApoE-/- mice, and the finding was supported by den Hartigh et al [16]. Further studies needed to investigate the effect of rapamycin on blood glucose in STZ plus high-fat diet-induced ApoE-/- mice.…”
Section: Discussionsupporting
confidence: 84%
“…Autophagy is essential to islet function and survival; on the contrary, inadequate autophagy can lead to islet degeneration and reduced insulin secretion [14, 15]. According to den Hartigh et al, low-grade chronic mTORC1 inhibition improved insulin sensitivity attributable to signaling through reduced phosphorylated p70S6K, which might be beneficial in antiobesity and anticardiovascular disease therapies [16]. AMPK, upstream of mTOR, exerts cardiovascular protective function by inhibiting mTOR [17].…”
Section: Introductionmentioning
confidence: 99%
“…There have been various animal models developed for investigating these diseases including inbred strains of mice with genetic manipulations that predispose them to disease [120][121][122][123]. Other manipulations and environmental exposures can be used to study the effects of comorbidities such as cigarette smoke-or drug (i.e., bleomycin)-induced pulmonary disease [124,125], paraquat-induced acute renal failure [126], repeated low-dose cisplatin treatment-induced chronic renal failure [127], streptozotocin-developed type I diabetes mellitus [128], and high fat/sucrose dites-induced insulin resistance, which is closely linked with type II diabetes melilitus, obesity, and cardiovascular disease [129,130]. The chemical/diet-induced disease methods can be applied to hACE2 Tg mouse models before infecting the SARS-CoV-2 to elucidate the association between comorbidity and the symptoms or pathogenesis of COVID-19.…”
Section: Validation Of the Risk Factors Associated With The Severe Symentioning
confidence: 99%
“…In many studies, chronic daily administration and, especially, intermittent or low-dose administration of rapamycin or everolimus did not cause hyperglycemia 7,54,70,131134 . In some studies, chronic treatment with rapamycin caused insulin resistance or glucose intolerance without insulin resistance, but also insulin sensitization with glucose intolerance 28,39,70,122,135 . The effects of rapamycin depend on its dose, duration of administration (especially), route of administration, time of administration, species and/or strain, sex, diet, obesity, and other factors.…”
Section: Why Rapamycin-induced Metabolic Alterations Varymentioning
confidence: 99%